Host-parasite interactions between Borrelia burgdorferi s.l. and its avian reservoir hosts - Norte, A.C. (2020)
Borrelia burgdorferi sensu lato (s.l.) is maintained in enzootic cycles in nature by vertebrate reservoir hosts, including mammals, lizards and birds. To understand the eco-epidemiology of Lyme borreliosis it is necessary to evaluate the relationships among Borrelia genospecies, their tick vectors and vertebrate reservoir hosts. We surveyed infection prevalence in avian hosts and using wild birds as models, we performed transmission experiments, assessed the physiological impact of infection in reservoir hosts and how exposure to stress could affect the host’s infectivity to vector ticks. Additionally, we evaluated the population structure of an avian-associated Borrelia genospecies.